2021
DOI: 10.1136/bmjopen-2020-047941
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriinfection-induced changes in the intestinal microbiota of 14-year-old or 15-year-old Japanese adolescents: a cross-sectional study

Abstract: ObjectiveThe relationship between Helicobacter pylori and the intestinal microbiota has not yet been clearly demonstrated in children and adolescents. The present study aimed at evaluating how H. pylori infection could affect the intestinal microbiota in adolescents using genetic analysis.DesignCross-sectional study.Setting and participantsWe included subjects from a longitudinal project involving H. pylori screening and treatment of junior high school third-grade students (aged 14 or 15 years) in Saga Prefect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…We compared the fecal intestinal microbiota of H. pylori -infected and noninfected children ( 13 ). Most studies on the effects of H. pylori on the intestinal microbiota based on the analysis of fecal samples were conducted in adults, and data from children are lacking ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the fecal intestinal microbiota of H. pylori -infected and noninfected children ( 13 ). Most studies on the effects of H. pylori on the intestinal microbiota based on the analysis of fecal samples were conducted in adults, and data from children are lacking ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the effects of H. pylori infection on the intestinal microbiota of children ( 13 ). This study included 80 H. pylori -infected and 79 noninfected 15-year-old adolescents.…”
Section: Association Between Mets and H Pylori In ...mentioning
confidence: 99%
“…A study on children showed that the abundance and diversity of gastrointestinal flora were higher in children without H. pylori infection, among which Proteobacteria, Bacteroides, Clostridium, etc., w ere more abundant ( Llorca et al., 2017 ). However, another study found that compared with uninfected children, H. pylori -positive children had an increased number of intestinal flora, such as Proteus, Clostridium, Firmicutes , and Prevotella ( Kakiuchi et al., 2021 ). Lu found that the diversity of intestinal flora in H. pylori -infected patients was higher, in which the abundance of Alistipes and Enterobacter cloacae increased and the abundance of Lachnoclostridium decreased.…”
Section: Effects Of H Pylori Infection On Gastroin...mentioning
confidence: 99%
“…Third, we analyzed the effects of H. pylori infection on the intestinal microbiota of children. 10 This study included 80 H. pylori -infected and 79 noninfected 15-year-old adolescents. No significant differences were observed in sex, age, and body mass index between the 2 groups.…”
mentioning
confidence: 99%
“…We speculate that this increase in the prevalence of Prevotella genus is associated with the increase in body mass index and glucose intolerance. 10 , 11 …”
mentioning
confidence: 99%